An Approach to Translation Didactics of English-Spanish Scientific and Technical Texts - Gómez, Norman; Gómez, Jorge Iván (Íkala, Revista de Lenguaje y Cultura, 2011)
This article shows some reflections obtained from the project ''Approximation to the translation of scientific and technical texts''. The project was carried out following these steps: search and selection of curricular information and readings about translation as a theoretical support for the proposal; creation of the Handbook for Teaching Translation of Scientific and Technical Texts: English/ Spanish, including its learning portfolio to evaluate its workshops; testing of some workshops and implementation of strategies for its divulgation. This project evidenced the shortage of programs for studying translation of scientific and technical texts in Colombia; the lack of consensus in the conceptualization of the text types referred as specialized languages and the need for revising the rigid structure followed, in general, by the existing translation handbooks. This handbook can be used in different translation settings, thanks to the universality of the technical and scientific languages and to the features it presents. However, it is necessary to continue testing its results in different settings in order to deepen in the research of the didactics of translation.